2000
DOI: 10.1002/1520-636x(2000)12:8<637::aid-chir6>3.0.co;2-w
|View full text |Cite
|
Sign up to set email alerts
|

?-Agonist-induced alterations in organ weights and protein content: Comparison of racemic clenbuterol and its enantiomers

Abstract: Clenbuterol is a relatively selective beta2-adrenergic partial agonist that has bronchodilator activity. This drug has been investigated as a potential countermeasure to microgravity- or disuse-induced skeletal muscle atrophy because of presumed anabolic effects. The purpose of this study was to: 1) analyze the anabolic effect of clenbuterol's (-)-R and (+)-S enantiomers (0.2 mg/kg) on muscles (cardiac and skeletal) and other organs; and 2) compare responses of enantiomers to the racemate (0.4 mg/kg and 1.0 mg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0

Year Published

2001
2001
2015
2015

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 36 publications
(17 citation statements)
references
References 44 publications
(46 reference statements)
2
15
0
Order By: Relevance
“…It suggests that both CB enantiomers were actively anabolic to striated muscle without much difference. These results were almost the same as the data of von Deutsch et al 8) using high dose rac-CB (1mg/kg) despite an age difference. The anabolic effect on muscles might depend on various mechanisms of hypertrophy like the balance of protein synthesis and proteolysis, and might be different from the effects on bone.…”
Section: Body Weights Of Rats In Three Groups Are Shown the Filled Dsupporting
confidence: 90%
See 4 more Smart Citations
“…It suggests that both CB enantiomers were actively anabolic to striated muscle without much difference. These results were almost the same as the data of von Deutsch et al 8) using high dose rac-CB (1mg/kg) despite an age difference. The anabolic effect on muscles might depend on various mechanisms of hypertrophy like the balance of protein synthesis and proteolysis, and might be different from the effects on bone.…”
Section: Body Weights Of Rats In Three Groups Are Shown the Filled Dsupporting
confidence: 90%
“…CB is well known as a lipolytic agent 22,23) . In the present study, the change of fat mass or liver, which is closely related to lipolysis and energy metabolism, was not examined; but von Deutsch et al 8) and Smith 24) reported that (+)-S-CB remains in higher concentration than (-)-R-CB in the liver. The liver weight of rats was negatively affected by a high dose (2.0 mg/kg daily) of CB drinking for 4 days 25) .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations